Community gardens as public art - Mateusz Salwa (Aisthesis, 2022)
The aim of the article is to discuss community gardens as works of public art. Even if artistic status of gardens has been widely recognized, it is usually taken into account when historic gardens and parks or works of contemporary landscapes architects are concerned. However, there are good reasons to approach community gardens as artworks, as well. First, aligning community gardens with contemporary art is honorific, in the sense that it shows that they may be considered in another way than seeing them only as vernacular art, significant because of its social and political dimension. Second, in spite of their allegedly edenic character, community gardens are very often contested spaces, while the conflicts may be sparked by, among other things, the community garden aesthetics. In order to recognize community gardens as art it is useful to refer to new genre public art and not to “paradigmatic arts” such as architecture or painting.